Kerala Model Of Health – Whether Good Health At Low Cost? - Manjusha P & Manju S. Nair
The widely acclaimed Kerala’s ‘good health at low cost’ model of health implies that it was possible, at low levels of resources, to achieve, commendable health status in the first three decades of inception of the state. However, the present situation raises serious doubts about the sustainability of Kerala ‘model’ of health. The simultaneous presence of the diseases of poverty (infectious diseases) and diseases of affluence (life style diseases), decay in Public Health System, uncontrolled growth of private sector resulting in escalation of health care cost etc are indicative of the deterioration in the Kerala model of health.